Revitalisasi Bahasa Indonesia melalui Neologisme dalam Penulisan Artikel Jurnal Bidang IPTEK - Sulistiyarini, Siti; Masrukhi, Moh. (Humanis; Vol 28 No 2 (2024), 2024)
This research aims to determine the use of neologisms to revitalize the Indonesian language in writing journal articles in science and technology and to describe the types of morphological processes of the forms of neologisms found. This research uses descriptive methods with a mixed approach. The data used are science and technology terms, including Indonesian neologisms in science and technology journal articles indexed by Sinta 2, which were collected using reading and note-taking techniques. Morphosemantic study to see the process of forming neologisms in science and technology and the changes in meaning that occur. As a result, three types of morphological processes were found that were used to form neologisms in science and technology: composition, affixation, and abbreviation. Then, the aim of forming neologisms is predominantly as equivalent forms of terms from foreign languages. This also supports the revitalization of the Indonesian language.